Poverty in the context of value-orientation self-facial: methodological approaches - Vasyutynsky, V. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
According to the results of analyzing the methodological approaches to a study of poverty, a conclusion about importance of determination of subjective poverty criteria was done. As the most effective research methods the psycho-semantic ones, content-analysis, interview, case-study, mass questioning, expert evaluation, and personality questionnaires were considered.